Identifikasi Aliran Sampah di Kota Semarang Melalui Pengelolaan Sampah Berbasis Masyarakat - Ramadan, Bimastyaji Surya; Fauziyah, Fita; Budihardjo, Mochamad Arief; Syafrudin, Syafrudin (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2019)
Community-based  waste  management  is a form  of  waste  management  recommended  by  the government because  it  is  very  effective  in  creating  a  zero-waste  society.  In  Indonesia,  community-based  waste management can be realized through the development of waste banks at the neighbourhoodlevels. In 2019, the City of Semarang has 48 units of active waste banks. Waste that is managed by the wastebank is plastic, paper and metal. However, there is organic waste which is also managed by several wastebanks. The purpose of this study is to identify and analyze the flow of waste through community-basedwaste management, in this  case of the  waste  bank,  in  the  city  of  Semarang.  The  method  used  is  in-depth  surveys  and  interviews related to the waste bank management system in the city of Semarang. The results showed that the activity of the existing garbagebank was able to reduce waste in the city of Semarang by 0.07% of the total garbage generation  in  the  city  of  Semarang.  This  research  can  be  used  as  a  reference  for  developing  better community-based waste management strategies, especially in Semarang City